Assessment of groundwater pollution in relation to heavy metals of the alluvial aquifer of Thriasion Plain (NW Attica) - Kyriazis, D.; Zagana, E.; Stamatis, G.; Fillippidis, F.; Psomiadis, E. (Bulletin of the Geological Society of Greece, 2013)
In this study the hydrogeological and hydrochemical characteristics of Thriasion Plain are presented focusing mainly on the presence of heavy metals in the alluvial aquifer. Two main aquifer systems exist in the study area: a) the karst aquifer hosted in the karstified carbonate formations, which structure the bedrock and the margins of the alluvial basin and b) the phreatic aquifer within the Quaternary deposits of the Thriasion Plain. Coastal and submarine groundwater discharges show the direct connection of the aquifers with the sea causing intense salinization in both aquifers. The phreatic aquifer is characterized by high levels of TDS (483 – 13,067 mg/l) and correspondingly high degree of hardness (15.7 to 165.7 odH). High concentrations of Na+, Cl-, SO4 2-, NO3 -, NH4 + and PO4 3- reflect the diverse anthropogenic influences on the aquifer. The strong presence of heavy metals, Cd, Cu, Fe, Mn, Ni, Pb, Sr and Zn has been determined in the most of the samples. Their origin is associated with geogenic factors, such as the occurrences of bauxites, oxides derived from the alteration of rocks, especially shischts, organic matter within the Plio-Pleistocene sediments of the region, as well as with intense pressures from anthropogenic activities. In some cases the groundwater is improper not only for human consumption but also for many other uses.